An Analysis of Conceptual Understanding of Depression among The Saudi Arabian Community in London - Nouf Mohammed Alyahyan (Journal of Educational and Human Sciences, 2023)
Depression is one of the most prevalent psychiatric disorders, and despite the recent waves of Saudi Arabian immigration into London, there is a dearth of information concerning the cultural perceptions of Saudi citizens regarding depression. Cross-cultural literature on depression is difficult to interpret because of the discrepancies in the conceptualizations and methodology used to study it. It is generally accepted, however, that an individual’s understanding of depression is largely determined by the social and cultural context in which they live. This study explores whether Saudi nationals in London hold traditional cultural views regarding depression and whether demographic factors and level of acculturation influence the degree to which those beliefs are espoused. Eighty-two adult Saudi nationals were recruited to complete a demographics sheet, questions regarding acculturation, and a Likert scale to assess their perceptions of depression. A regression analysis indicated that the respondents moderately supported their culture’s most known traditional beliefs regarding depression. However, neither the demographic factors nor the number of years in the UK contributed to the variance of those traditional beliefs, and only the frequency with which the English language was used at home predicted the agreement with traditional views regarding depression. This study found that some measurements of acculturation predicted stronger Saudi Arabian cultural beliefs about depression in the sample. Results must be interpreted with caution due to the study’s exploratory nature, and further research is warranted to explore the implications for clinical practice fully.